Use your mobile computing devices to learn - Contextual mobile learning system design and case studies - Chuantao Yin; David, B.; Chalon, R. (2009 2nd IEEE International Conference on Computer Science and Information Technology, 2009)
In recent years, with the rapid development of mobile computing technologies, a new learning style-mobile learning has exploded everywhere in our society, which is considered as an essential learning style in the future. This paper presents a mobile learning system taking into account learning context, which is also called contextual mobile learning. With the help of this system, we can learn just in time in our daily lives whenever we need to learn, using mobile computing devices like Tablet PCs and PDAs. The main principles and the development process such as production of learning units and continualization process are presented. Two case studies are introduced to apply the system in concrete scenarios.